Legal Liability in Property Credit Agreements: Analysis of Default Risk and Debtor Protection from a Contractual Justice Perspective - Fahri Adam; Z. Zainuddin; Ilham Abbas (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to analyze the construction of legal liability in property credit agreements, emphasizing the risk of default and debtor protection from a contractual justice perspective. The main focus of the study is directed at how the distribution of risk in credit agreements affects the assignment of legal liability, as well as the extent to which the principle of contractual justice is accommodated in banking practice. This study uses a normative legal research method with a statutory regulatory approach and a conceptual approach. The legal materials used include primary, secondary, and tertiary legal materials, which are analyzed descriptively and prescriptively to identify legal problems and formulate equitable normative solutions. The results show that the construction of property credit agreements in Indonesia is still dominated by standard agreements that tend to place debtors in a weak position, resulting in disproportionate legal liability for default. The risk of default is not only caused by individual debtor factors, but also by information imbalances, creditor dominance in contract drafting, and the influence of macroeconomic factors. Furthermore, debtor protection mechanisms in practice are still limited, both in terms of contract substance and in the law enforcement process, particularly in the implementation of collateral execution. The findings of this study confirm the need for a reformulation of property credit agreements based on contractual equity, through increased transparency, more proportional risk distribution, and the development of more effective debtor protection mechanisms. Thus, legal accountability will no longer be an instrument that reinforces inequality, but rather a means to achieve balance and fairness in contractual relationships.